2006
DOI: 10.1002/bjs.5434
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of the effect of quilting latissimus dorsi flap donor site on seroma formation

Abstract: Quilting significantly reduced overall seroma volumes after LD breast reconstruction including extended LD, and is recommended in combination with surgical drains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 29 publications
4
45
1
Order By: Relevance
“…Seroma rates of 47 to 96 percent are reported. 98,99 Others have shown late reoperation rates of up to 50 percent as a result of implant-related complications. 100 Donor-site asymmetry can be significant if large volumes of tissue are harvested in overweight patients.…”
Section: Pedicled Latissimus Dorsi Flapmentioning
confidence: 98%
“…Seroma rates of 47 to 96 percent are reported. 98,99 Others have shown late reoperation rates of up to 50 percent as a result of implant-related complications. 100 Donor-site asymmetry can be significant if large volumes of tissue are harvested in overweight patients.…”
Section: Pedicled Latissimus Dorsi Flapmentioning
confidence: 98%
“…In addition to adduction, inward rotation and straightening the arm, it is also an auxiliary exhaust muscle (for example, it gets stretched during the cough). (Daltrey et al 2006) Using the part of latissimus dorsi muscle and transferring it as pedicle flap with soft tissues to the anterior wall of the chest may significantly influence torso symmetry, which has been confirmed in photogrammetric studies. However, the extent of torso statics disturbances after LD reconstruction is still unknown.…”
Section: Latissimus Dorsi Flap Reconstructionmentioning
confidence: 83%
“…Many researchers, through systemic reviews and meta-analyses, have shown the effectiveness of a combination of quilting sutures and FS [19][20][21][22][23]. In these studies, a combination of quilting sutures and FS significantly reduced the seroma rate, total drainage amount, drain removal time, and frequency of seroma aspiration.…”
Section: Discussionmentioning
confidence: 98%
“…Further, a quilting suture can successfully obliterate any dead space with tissue fixation and minimize the shearing force of the skin flap and the underlying structures [19][20][21]. Tissue adhesion with a quilting suture and the immobilization of the patient's shoulder can considerably minimize any dead space and the shearing force [20][21][22]. Quilting sutures can also reduce the spontaneous movement between the skin flaps and the underlying muscle, thus decreasing inflammation.…”
Section: Discussionmentioning
confidence: 99%